(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article provides an overview of the fund R-38 of the People’s Commissariat of Justice of the Turkestan ASSR, which is stored in the National Archives of Uzbekistan. In particular, the content, types and safety of archival documents stored in the fund are analyzed.